2012
DOI: 10.1074/jbc.c112.406769
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Tethering and Nucleotide-dependent Conformational Changes Drive Mitochondrial Genome Maintenance (Mgm1) Protein-mediated Membrane Fusion

Abstract: Background: Dynamin proteins shape membranes by promoting membrane curvature, fission, and fusion. Results: Cryo-EM demonstrates how the dynamin-related protein Mgm1 assembles onto and tethers membranes followed by nucleotide-dependent conformational changes. Conclusion: Mgm1 may mediate mitochondrial fusion by bridging opposing membranes and undergoing structural transitions. Significance: This study provides new mechanistic details of how dynamins may function as fusion molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 33 publications
3
18
0
Order By: Relevance
“…Wild-type s-Mgm1 and S244A (a previously characterized GTP binding mutant [24]) were found to co-localize with liposomes, suggesting that they were recruited and assembled onto liposomes ( Fig. 5a and b), similar to previous observations by electron microscopy [28]. Consistently, K795A (a previously characterized lipid binding mutant [24]) aggregated out of the solution (Fig.…”
Section: S-mgm1 Promotes Local Membrane Bendingsupporting
confidence: 83%
See 3 more Smart Citations
“…Wild-type s-Mgm1 and S244A (a previously characterized GTP binding mutant [24]) were found to co-localize with liposomes, suggesting that they were recruited and assembled onto liposomes ( Fig. 5a and b), similar to previous observations by electron microscopy [28]. Consistently, K795A (a previously characterized lipid binding mutant [24]) aggregated out of the solution (Fig.…”
Section: S-mgm1 Promotes Local Membrane Bendingsupporting
confidence: 83%
“…Unlike a soluble isoform of OPA1, which has been shown to cause liposome tubulation, s-Mgm1 has been reported to only assemble on the membrane as a crystalline array, failing to initiate liposome tubulation [25][26][27]. We demonstrated that, similar to atlastin and the mitofusins, s-Mgm1 tethers membranes and undergoes a striking GTP-dependent structural transition that might be the mechanism to promote membrane fusion [28]. Since the fundamental difference between pro-fusion and pro-fission dynamins is that the pro-fusion dynamins are membrane anchored, it is plausible that the transmembrane domains of the mitofusins, atlastin, and l-Mgm1 are essential for destabilizing the phospholipid bilayer in order to facilitate fusion.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Interestingly, when soluble Mgm1 is mixed with CL-containing and Mgm1-embedded liposomes, the GTPase activity of soluble Mgm1 is further increased due to interactions with both CL and the membrane form of Mgm1. Interactions of Mgm1 with phospholipids are not specific to CL, as Mgm1 can tubulate and tether liposomes and promote GTP-stimulated hemifusion of liposomes independently of CL [105]. This type of non-selective interaction with phospholipids and the activation of GTPase activity were also observed for Opa1, which is a mammalian ortholog of Mgm1, as discussed below.…”
Section: Roles Of Phospholipids In Mitochondrial Dynamicsmentioning
confidence: 99%